Efek Game Online dalam Mempengaruhi Sikap Sosial Anak Sekolah Dasar - Aida Rahmi Nasution; Tika Meldina; Erwanto Erwanto; Diah Yupita Sari (AR-RIAYAH : Jurnal Pendidikan Dasar, 2022)
The rapid development of technology today does not fully have a positive impact on children. The breadth of access to online games, the ease of access and operationalization make children forget the time when playing them. This is a concern for all groups including parents, because online games have penetrated the family as well as school level. The fun effect of playing online games turns out to have an impact on children's low social attitudes. This research was conducted to explore and prove the extent to which children are addicted to online games and how much influence online games have on children's social attitudes. This study uses a quantitative non-experimental design approach. The research sample was 25 people who were assigned randomly (randomly). The methods used are interviews and questionnaires. Data analysis techniques in this study consisted of validity test, reliability test, normality test, homogeneity test, and linear test. While data analysis using hypothesis testing includes simple linear regression test, and test the coefficient of determination. The results of the study reveal that the effect of online games has a significant effect on children's social attitudes as evidenced by the results of simple linear regression where the output is known to be calculated F value = 18.966 with a significance level of 0.000 <0.05. This data recommends that there is an influence of online games (X) on social attitudes (Y), this data is also proven from the calculation of the coefficient of determination (R Square) of 0.963, which explains that the independent variable (online games) on the dependent variable (social attitudes) is 96 .3% of children's social attitudes are influenced by online games and the category is very high.